DIFFERENTIATION-BASED LEARNING: UNDERSTANDING INDIVIDUAL DIFFERENCES IN LEARNING STRATEGIES - Mulasi, Syibran; Mujiburrahman, Mujiburrahman; Habiburrahim, Habiburrahim; Silahuddin, Silahuddin; Md Ghazali, Nor Hasnida (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2025)
Understanding learning theories and individual learning differences is an important aspect in designing and implementing effective learning strategies. This article explores the relationship between learning theories and individual differences in learning contexts. Through an in-depth theoretical review, this article reviews several major learning theories, including behaviorism, constructivism, social cognitive theory, and cognitive load theory. Next, this article discusses various factors that influence individual differences in learning, such as cognitive abilities, learning styles, motivation, interests, and cultural background. The method used is typeliterature study with the aim of exploring research related to the theme of Differentiation-Based Learning and individual differences in developing learning strategies. The study was carried out starting with the stages of collecting and analyzing various previous studies that were relevant to understanding how differentiation-based learning strategies work, and also identifying and collecting articles, journals, books, and academic publications discussing relevant theories. Data sources were taken from academic databases such as Google Scholar (journals), JSTOR, and ProQuest, as well as other references. Next, a literature analysis was carried out, the selected literature was analyzed using the content analysis method to identify main themes, significant findings, and the methodology used in previous research. The research results found that the exploration of effective learning strategies was also a focus with an emphasis on developing a differentiation approach to meet the needs of the diverse learning styles of each student. By integrating learning theories and understanding individual differences, a teacher can create an inclusive learning climate that supports all students, increases their learning potential, and achieves higher academic goals.